Antileukemic effects of neurokinin-1 receptor inhibition on hematologic malignant cells: a novel therapeutic potential for aprepitant. Issue 3 (March 2018) - Bayati, Samaneh; Razani, Elham; Bashash, Davood; Safaroghli-Azar, Ava; Safa, Majid; Ghaffari, Seyed H.
Abstract : Genetic and laboratory studies have remodeled the conventional understanding of cancer pathogenesis by identifying different molecular alterations. Intrigued by the contribution of neurokinin-1 receptor (NK1R) network in cancer pathogenesis, we investigated the antileukemic effects of aprepitant, a nonpeptide antagonist of NK1R, in a panel of hematological cell lines. In this study, we found that aprepitant decreased the survival of all the tested cells; however, as compared with NB4, viability of the other cell lines was inhibited at higher concentrations. By increasing both p21 and p73 along with suppressing c-Myc and hTERT, aprepitant probably disordered cell distribution in the cell cycle, decreased DNA replication rate, and, thereby, impeded the proliferative capability of NB4 cells. Moreover, exposing cells to this agent led to activation of the caspase-3-dependent apoptotic pathway through altering the expression of apoptosis-related genes. Noteworthy, aprepitant also sensitized NB4 cells to the cytotoxic effects of arsenic trioxide and vincristine. Overall, it seems that pharmaceutical targeting of NK1R using aprepitant, either as a single agent or in combination, possesses novel promising potential for leukemia treatment strategies.